WYPiWYG hyperelasticity without inversion formula: Application to passive ventricular myocardium. (June 2017) - Latorre, Marcos; Montáns, Francisco J.
Highlights: A general method for spline-based hyperelasticity without inversion formula. The approach is valid for isotropy and anisotropy. There are no explicit material parameters. A complete set of tests defining the material behavior may be exactly captured. Application to passive ventricular myocardium. Abstract: WYPiWYG hyperelasticity is a family of computational procedures for determining the stored energy density of soft materials. Instead of assuming the global analytical shape of these functions (the model), they are computed solving numerically the differential equations of a complete set of experimental tests that uniquely define the material behavior. WYPiWYG hyperelasticity traditionally uses an inversion formula to solve the differential equations, which limits the possible types of tests employed in the procedure. In this work we introduce a new method that does not need an inversion formula and that can be used with any type of tests. We apply the new procedure to determine the stored energy function of passive ventricular myocardium from five experimental simple shear tests.